Pengaruh Persepsi Siswa Tentang Tata Tertib Sekolah Terhadap Kedisiplinan Siswa Di Madrasah Aliyah Negeri 1 Mukomuko - Rahmah, Yulia Gina; Yusri, Nur Aisyiah; Aulia, Rahmadianti (Batanang : Jurnal Psikologi, 2023)
This research was motivated by the large number of students who committed disciplinary violations based on guidance counseling records and disciplinary team data at Madrasah Aliyah Negeri 1 Mukomuko, from the results of interviews with four students, there were differences in perceptions about school rules for each student, this could be a one of the causes of disciplinary violations, which is caused by differences in perceptions that there are rules that are not properly implemented. This study aims to see whether there is an influence of student perceptions of school discipline on student discipline at Madrasah Aliyah Negeri 1 Mukomuko.This study uses quantitative methods with simple regression analysis. The population in this study were all students of Madrasah Aliyah Negeri 1 Mukomuko and a sample of 174 students of class X & XI Madrasah Aliyah Negeri 1 Mukomuko. Sampling in this study used a proportionate stratified random sampling technique. The data collection technique uses a psychological scale from a 4-level model scale or 4 answer choices, namely the perception scale and the disciplinary scale.The results of the analysis reveal that students' perceptions of school discipline at Madrasah Aliyah Negeri 1 Mukomuko are 67% in the low category and the level of student discipline at Madrasah Aliyah Negeri 1 Mukomuko is 60% in the low category, while 40% are in the high category. Then perception only has as much as 2.6% influence on discipline, which means 97.4% is influenced by other variables. Furthermore, students' perceptions of school discipline have an influence on student discipline.┬áKeyword: Discipline, Perception